Phytopharmacological potential of the natural gift Moringa oleifera Lam and its therapeutic application: An overview - Sakthivel Lakshmana Prabu; Appavoo Umamaheswari; Ayarivan Puratchikody (Asian Pacific Journal of Tropical Medicine, 2019)
Traditionally, medicinal plants of family Moringaceae have been well-recognized due to their multipurpose utilization in various fields such as treatment of several diseases for they have a broad range of pharmacological activities, in wastewater treatment as well as food source. Fractionation of this medicinal plants and its bioactivity study discloses the presence of several phytoconstituents and secondary metabolites like terpenes, flavonoids, steroids, phenolic compounds, tannins, carohydrates, flavonoids, vitamins and minerals. The results of bioactivity study results revealed that different extracts such as aqueous, methanolic and ethanolic of Moringa oleifera showed notable therapeutic activities. Our present review explore and focus on the phytochemical composition and various pharmacological activities like immunomodulator, antidiabetic, antiulcer, anthelmintic, anti-inflammatory, antipyretic, analgesic, antiepileptic, cardioprotective, lipid lowering, antihypertensive, hepatoprotective, anti-nephrotoxicity and anti-microbial activities to arouse public consciousness about the nutritional and medicinal value of this “miracle tree - Moringa oleifera” in favor of humanity.